(untitled) (Portuguese Journal of Family Medicine and General Practice, 2015)
Introduction: The prevalence of lower urinary tract symptoms (LUTS) increases with age. They have significant impact on quality of life and commonly cause adults to seek medical care. When a middle-aged man presents with LUTS, we must consider diseases that affect the prostate, urethra, bladder and detrusor muscle. Case report: A 50 year-old male welder, with a previous history of dyslipidemia, 3,5 pack-years of smoking, and an episode of renal colic with renal microlithiasis came to his Family Physician in October 2012. He complained of dysuria, urinary frequency, terminal hematuria, and hypogastric pain. A diagnosis of cystitis was made and antibiotic therapy was prescribed after obtaining a urine culture. The urine culture was negative. In the absence of prostration, fever, and purulent discharge, and given a previous history of urolithiasis, this episode was reinterpreted as a second episode of renal colic. In August 2013, the patient presented with terminal dribbling, sporadic dysuria, and hematuria on urine dipstick analysis. An assay of total prostate specific antigen, an analysis of urinary sediment, and a transabdominal vesicoprostatic ultrasound were ordered. One month later a bulky neoplastic lesion of the bladder was found on ultrasound examination. Comment: Despite the presence of risk factors for bladder carcinoma (previous smoking and age over 35 years), this diagnosis was not considered at the initial consultation. On follow-up, other confounding factors emerged, including a past history of renal stones and the presence of symptoms suggestive of other diseases more common in this age group. The case report explores the complexity of the differential diagnosis of LUTS in an adult male. This is a common complaint in Family Medicine consultations, pointing to a set of disorders with defined diagnostic and therapeutic guidelines.